INFLUENCE OF PRINTING AND LOADING DIRECTION ON MECHANICAL RESPONSE IN 3D PRINTED MODELS OF HUMAN TRABECULAR BONE - Tomáš Doktor; Ivana Kumpová; Sebastian Wroński; Maciej Śniechowski; Jacek Tarasiuk; Giancarlo Forte; Daniel Kytýř (Acta Polytechnica CTU Proceedings, 2018)
The paper deals with investigation on directional variations of mechanical response in 3D printed models of human trabecular bone. Sample of trabecular bone tissue was resected from human donor and 3D model was obtained by X-ray computed tomography. Then a series of cubical samples was prepared by additive manufacturing technique and tested by uniaxial compression loading mode. Mechanical response was compared in nine different combinations of direction of 3D printing and loading direction. The results show neglectible influence on the deformation response in elastic region (stiffness) and significant changes of the behaviour in plastic region (stress and strain at yield point, strain at full collapse).